Comparative study of cycle modification strategies for trans-critical CO2 refrigeration cycle for warm climatic conditions. (March 2016) - Singh, Simarpreet; Purohit, Nilesh; Dasgupta, M.S.
Abstract: This paper presents a comparative study of performance of six prominent modifications on the basic trans-critical CO2 refrigeration system to investigate their suitability to high ambient temperature application (35–55 °C). To explore the application in chiller, domestic refrigeration and air cooling the evaporator temperature chosen are −10 °C, 0 °C and 10 °C respectively. In general the cycle modifications have a positive effect on the overall COP of the system. However, to comprehend practicability of these modifications for three application areas, a few other parameters which affect design and operation are also included in the study. These are compressor discharge pressure and temperature, mass flow rate, interstage pressure for multi-stage operation and exergy destruction. Effect of real time constraints like approach temperature, pressure drop in gas cooler, compressors efficieny, degree of superheat, expanders efficiency and effectivenesss of intermediate heat exchanger are also incorporated. Interrelation between these parameters are brought out from the study.